Analysis of Blood Glucose Profiles Based on Physical Activity Levels Among Residents - Galih Yoga Santiko; Arief Darmawan; Yudhi Teguh Pambudi; Izzul Fikar Ramadha (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to analyze blood glucose profiles based on physical activity levels among residents of Waluyorejo Village, Puring District, Kebumen Regency, Indonesia. A quantitative descriptive approach with a field survey design was employed. A total of 25 adult respondents participated in the study, conducted from July to August 2025. Physical activity levels were assessed through direct observation of daily routines, including occupational activities, mobility patterns, and frequency of physical engagement, supported by short interviews to capture lifestyle history and dietary habits. Blood glucose levels were measured using a digital glucometer through fasting blood glucose (FPG) procedures to ensure measurement accuracy. The data were analyzed descriptively to identify patterns of blood glucose distribution across physical activity categories. The results revealed that the average blood glucose level among respondents was 110 mg/dL. Of the total participants, 32% were classified as normal, 52% as prediabetic, and 16% as diabetic. These findings indicate that a majority of the population is at risk of developing metabolic disorders, despite generally engaging in moderate to high levels of physical activity. The results suggest that physical activity alone is insufficient to maintain optimal glucose regulation without being accompanied by balanced nutritional intake and regular health monitoring. This study highlights the importance of integrating physical activity with comprehensive lifestyle management, including dietary control and routine health screening. The findings provide empirical evidence to support community-based health promotion programs aimed at preventing non-communicable diseases, particularly in rural settings.